2017
DOI: 10.3390/en10020182
|View full text |Cite
|
Sign up to set email alerts
|

How Do Dietary Choices Influence the Energy-System Cost of Stabilizing the Climate?

Abstract: Abstract:We investigate how different global dietary scenarios affect the constraints on, and costs of, transforming the energy system to reach a global temperature stabilization limit of 2 • C above the pre-industrial level. A global food and agriculture model, World Food Supply Model (WOFSUM), is used to create three dietary scenarios and to calculate the CH 4 and N 2 O emissions resulting from their respective food-supply chains. The diets are: (i) a reference diet based on current trends; (ii) a diet with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Livestock results in GHG emissions such as nitrous oxide, carbon dioxide, and methane due to high-energy feed production, concentrating production and enteric fermentation of ruminants ( 3 ). However, impacts related to ruminant meat are higher when compared to monogastric animals because of methane emissions and the need for substantial livestock feed production needed ( 43 , 50 , 51 ). As consumers in the Q5 of the provegetarian score ate less meat, especially ruminant meat, compared to participants in the other quintiles, the difference in GHG emissions is further increased.…”
Section: Discussionmentioning
confidence: 99%
“…Livestock results in GHG emissions such as nitrous oxide, carbon dioxide, and methane due to high-energy feed production, concentrating production and enteric fermentation of ruminants ( 3 ). However, impacts related to ruminant meat are higher when compared to monogastric animals because of methane emissions and the need for substantial livestock feed production needed ( 43 , 50 , 51 ). As consumers in the Q5 of the provegetarian score ate less meat, especially ruminant meat, compared to participants in the other quintiles, the difference in GHG emissions is further increased.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed food exhibiting increased consumption in SDI Q5 compared to SDI Q1 in our study are those classified in the green class (low greenhouse gas emissions relate to food production and high SNRF), while those with a decrease are in the red class (high greenhouse gas emissions relate to food production and low SNRF). Moreover, meats from ruminants are related to more greenhouse gas emissions, energy and land consumption compared to poultry, pork and eggs (2,4,50) that is why the relative differences in these food group consumption between SDI Q1 and SDI Q5 are lower than for red meat. Finally, it is noteworthy that for some food groups, such as fish, egg and dairy products, no consensus has emerged certainly due to the differences in methodological and arbitrary choices concerning the objective function and constraints of linear programming with conflicting views on nutrition (adequate nutrient intake), environment (fish stock collapse or livestock environmental impacts) and contaminant exposition (in particular from fatty fish).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed food exhibiting increased consumption in SDI Q5 compared to SDI Q1 in our study are those classified in the green class (low greenhouse gas emissions relate to food production and high SNRF), while those with a decrease are in the red class (high greenhouse gas emissions relate to food production and low SNRF). Moreover, meats from ruminants are related to more greenhouse gas emissions, energy and land consumption compared to poultry, pork and eggs ( 2 , 4 , 50 ) that is why the relative differences in these food group consumption between SDI Q1 and SDI Q5 are lower than for red meat.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have suggested that future temperature targets could be achieved without major reductions in ruminant/agricultural methane emissions (102,103,104), Roe et al [95], synthesising previous top-down and bottom-up estimates of mitigation in agriculture propose a 25% reduction in agricultural non-CO 2 emissions by 2050, compared to business as usual, in their implementation roadmap for the land sector.…”
Section: Methane Reduction In Climate Stabilization Pathwaysmentioning
confidence: 99%